Bubbles in Hybrid Markets - How Expectations about Algorithmic Trading Affect Human Trading - Mike Farjam; Oliver Kirchkamp (Center for Economic Studies and ifo Institute (CESifo), 2015)
Bubbles are omnipresent in lab experiments with asset markets. Most of these experiments were conducted in environments with only human traders. Today markets are substantially determined by algorithmic traders. Here we use a laboratory experiment to measure changes of human trading behavior if these humans expect algorithmic traders. To disentangle the direct effect of algorithmic traders we use a design where we manipulate only the expectations of human traders. We find clearly smaller bubbles if human traders expect algorithmic traders to be present.
Keywords: C92; G02; 330; bubbles; expectations; experiment; algorithmic traders